Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan di UD. Asih Konveksi - Rahayu, Desak Putu Lidya; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of work environment and work discipline on employee performance at UD. Asih Konveksi, both partially and simultaneously. This type of research is causal research with a quantitative approach. The population used is all employees at UD. Asih Konveksi. The sample used in this study was to use saturated samples or by making all the population into samples, namely 42 people. The type of data used is quantitative data with secondary and primary data sources. The data collection methods in this study were observation, interview, and also a questionnaire method with a Likert scale. The analysis technique used in this research is to use multiple linear regression analysis techniques with partial (t test) and simultaneous (F test) hypothesis testing. The results of this study indicate that (1) the work environment has a positive and significant effect on employee performance at UD. Asih Konveksi, (2) work discipline has a positive and significant effect on employee performance at UD. Asih Konveksi, and (3) the work environment and work discipline have a positive and significant effect on employee performance at UD. Asih Konveksi.